Calculation of stretching factor for optical pulse stretcher - Leshchenko, V.P.; Povrozin, A.I.; Karelin, S.Y. (Вопросы атомной науки и техники, 2014)
A task of temporal stretching of pulses in an optical pulse stretcher of CPA-laser systems is considered. The output
pulse profiles are obtained and the stretching factors are calculated on the foundation of the solution of the wave
equation for a passage through an optical stretcher of the ultrashort pulses with the different profiles. The calculations
for the optical stretcher of Offner triplet type had made. Рассмотрена задача о временном расширении импульсов в оптическом расширителе импульсов CPAлазерной системы. На основе решения волнового уравнения для прохождения сверхкоротких импульсов различного профиля через оптический расширитель импульсов получены их выходные профили и рассчитаны коэффициенты расширения. Расчеты выполнены для оптического расширителя типа триплета Оффнера. Розглянуто задачу про часове розширення імпульсів в оптичному розширювачі імпульсів CPA-лазерної системи. На основі рішення хвильового рівняння для проходження надкоротких імпульсів різного профiлю через оптичний розширювач отримано їх вихідні профілі та розраховано коефіцієнти розширення. Розрахунки виконанo для оптичного розширювача типу триплету Оффнера.